ASEAN COOPERATION INTOURISMTRAINING:VOICES OFTHAI AND VIETNAMESE SCHOOLS - HIEN, NGUYEN THUY (ITB Journal Publisher, LPPM ITB, 2010)
This study examined vocational teachers’ and administrators’ perception of ASEAN cooperation in tourism training and identify factors affecting their perception. A documentary and questionnaire were employed to collect data. At least 79 percent of respondents agreed that ASEAN information is disseminated widely, clearly, continuously and it is easy to recognize ASEAN publications among others. However, information about the regional cooperation in tourism training in particular was not considered to be adequate. Administrators and teachers in general had positive attitudes toward ASEAN cooperation. Yet while respondents did not appreciate the impact of differences in national culture and school formal organization procedures on ASEAN cooperation, the results of this research showed that nationality and school status do influence their perception, and thus, guide their behavior in cooperation. The data also revealed a fact that schools value resources that ensure quality of training provision rather than existing relations or financial resources of a potential partner.